Application of Wasted Oolong Tea as a Biosorbent for the Adsorption of Methylene Blue - Yunfei Hu; Yue Zhang; Yuqun Hu; Chen-Yao Chu; Jinke Lin; Shuilian Gao; Dongyi Lin; Jing Lu; Ping Xiang; Tzu-Hsing Ko (Journal of Chemistry)
Tea powder, a biosorbent prepared from wasted oolong tea, was collected as a prospective adsorbent for the adsorption of methylene blue (MB) from aqueous solution. The effect of factors on adsorption efficiency, isotherms, kinetics, and potential mechanism was carried out. Adsorption capacity of MB onto wasted tea powder increased with the MB concentration and contact time, whereas the increase in pH value and ion strength appeared to have a negative effect for the adsorption process. The adsorption efficiency increased rapidly and reached a stable state within 120 min. The optimal tea powder loading weight is suggested to be at 0.1 to 0.2 g, and the highest efficiency of 94.8% is achieved at 333 K. There were no significant changes in adsorption efficiency when the effect of temperature is considered. The Langmuir isotherm model was found to be the best isotherm models to elucidate the adsorption mechanism in this study. The maximum adsorption capacities calculated at different temperatures by the Langmuir model ranging from 312.5 to 333.3 mg·g−1 were much close to the experimental results. From the kinetic analysis, the pseudo--second-order model was found to be the best model to describe the adsorption behavior. The calculated adsorption capacities at different initial MB concentrations by the pseudo-second-order model ranging from 92.34 to 400 mg·g−1 were well close to the experimental data. The fitting results obtained from the intraparticle diffusion model suggested that the intraparticle diffusion was not the only rate-controlling step and some other mechanisms along with the intraparticle diffusion were probably involved. The intraparticle diffusion of MB molecules into pore structures of wasted tea powder is the rate-limiting step for the adsorption process in this study. The repetitive cycle experiments indicated that the wasted oolong tea powder was efficiently regenerated using NaOH and thus be used for many times.